Carbonylations and hydroformylations for fine chemicals - Kelkar, A. A. (Industrial catalytic processes for fine and specialty chemicals, 2016)
Carbonylation reactions (hydroformylation and carbonylation) constitute one of the most powerful tools for C. C bond formation in organic synthesis and represent an outstanding example of the application of homogeneous catalysis on an industrial scale. Carbonylation reactions have the potential to provide clean, atom-efficient routes for the synthesis of molecules with carboxylic acid, aldehyde and amide functional groups. However, catalyst product separation is a major problem for the application of homogeneous catalysts on an industrial scale. The manufacture of ibuprofen, one of the important antiinflammatory drugs involving palladium-catalyzed carbonylation, was the path-breaking technology in pharmaceutical chemistry. A significant amount of work is being carried out on the development of selective catalysts for specialty chemical synthesis. This chapter presents recent advances in the development of new catalysts for carbonylation reactions. Various strategies developed for the heterogenization of catalysts are also presented, with an emphasis on specialty chemicals.

MgFeCe ternary layered double hydroxide as highly efficient and recyclable heterogeneous base catalyst for synthesis of dimethyl carbonate by transesterification - Nivangune, N. T. (Catalysis Letters, 2017)
A series of Mg3:Fex + Ce1−x LDHs (3:1) were synthesized by co-precipitation method by varying molar ratio of Fe:Ce between 1:0 to 0:1 (LDH-1 to LDH-6). All synthesized LDHs were characterized by XRD, FT-IR, TEM, N2 sorption, benzoic acid titration and XPS in detail and evaluated for selective synthesis of dimethyl carbonate by transesterification of ethylene carbonate with methanol. It was demonstrated that the structural and basic properties of synthesized LDHs were strongly dependent on the Fe:Ce molar ratio (Ce concentration). The correlation between their physicochemical properties and catalytic performance was studied in detail. Among all synthesized LDHs the best result was obtained with LDH-3 (Fe:Ce = 0.85:0.15) where LDH structure remained intact, and showed high number of strong basic sites on LDH surface. LDH-3 was recycled 7 times while maintaining high catalyst activity and selectivity towards DMC. The obtained results elucidate the important role of Ce in modifying the basic properties of LDH in enhancing the catalytic activity for DMC synthesis. Graphical Abstract: [Figure not available: see fulltext.]. © 2017, Springer Science+Business Media, LLC.
Keywords: Dimethyl carbonate; ethylene carbonate; Mg–Fe–Ce Ternary Hydrotalcite; transesterification